Late Holocene ice-wedge polygon dynamics in northeastern Siberian coastal lowlands - Schirrmeister, Lutz (Dr.); Bobrov, Anatoly; Raschke, Elena; Herzschuh, Ulrike (Prof. Dr.); Strauss, Jens; Pestryakova, Luidmila A. (Prof. Dr.); Wetterich, Sebastian (Arctic, Antarctic, and Alpine Research, 2018)
Ice-wedge polygons are common features of northeastern Siberian lowland periglacial tundra landscapes. To deduce the formation and alternation of ice-wedge polygons in the Kolyma Delta and in the Indigirka Lowland, we studied shallow cores, up to 1.3 m deep, from polygon center and rim locations. The formation of well-developed low-center polygons with elevated rims and wet centers is shown by the beginning of peat accumulation, increased organic matter contents, and changes in vegetation cover from Poaceae-, Alnus-, and Betula-dominated pollen spectra to dominating Cyperaceae and Botryoccocus presence, and Carex and Drepanocladus revolvens macro-fossils. Tecamoebae data support such a change from wetland to open-water conditions in polygon centers by changes from dominating eurybiontic and sphagnobiontic to hydrobiontic species assemblages. The peat accumulation indicates low-center polygon formation and started between 2380 +/- 30 and 1676 +/- 32 years before present (BP) in the Kolyma Delta. We recorded an opposite change from open-water to wetland conditions because of rim degradation and consecutive high-center polygon formation in the Indigirka Lowland between 2144 +/- 33 and 1632 +/- 32 years BP. The late Holocene records of polygon landscape development reveal changes in local hydrology and soil moisture.